Does the use of Beef-on-Dairy lead to increased longevity in dairy herds? - L. Hüneke; C. Schmidtmann; S. Rensing; G. Thaller; J. Heise (Animal, 2025)
The genetic progress of longevity in Holsteins has been very strong over the last years; however, the phenotypic longevity only increases moderately. It is often argued that this discrepancy between genetic and phenotypic longevity can mainly be explained with the availability of too many replacement heifers on the farms. Following this hypothesis, a farmer would rather prematurely cull a cow from the herd than the freshly calved heifer. The availability of dairy replacements on the other side depends on other management decisions: rate of born female dairy calves, rate of losses, sales and purchases of female dairy calves. The rate of born female dairy calves is influenced largely by (a) the use of sexed semen and (b) the use of beef semen on dairy cows (BoD). In our study, we analysed, whether herds with a lower rate of born female dairy calves (and therefore less available replacement heifers) have higher average longevity of cows. The data set comprised 2 784 880 calving records and 1 025 203 disposals, resulting in data of 10 627 German herds. These herds were clustered into groups based on (1) the proportion of BoD use and (2) the proportion of female dairy calves born in 2020/2021. The average longevity of cows culled in 2022/2023 (replaced by calves born in 2020/2021) was compared. The genetic level (Estimated breeding value of longevity) did not differ significantly between the categories of farms nor did the average production level (milk yield) per herd. A significant association was found between BoD use and phenotypic longevity: herds with high BoD use (> 20%) had an average longevity that was 147 days longer than that of herds with no BoD use (< 2%). Similarly, herds with a lower proportion of female dairy calves born had a significantly higher average longevity: herds with > 55% female dairy calves (thus, a high number of possible replacement heifers) had an average longevity of 1 197 days, whereas herds with < 40% female dairy calves had an average longevity of 1 335 days. This strong increase in average longevity related to the reduction of possible replacements indicates that many cows are culled early due to management decisions rather than due to health issues and other functional reasons.